Prototyping a Web-Based Application for Remedial Education Data Management - Haruna, Isyaku Uba; Awang, Hapini; Mansor, Nur Suhaili; Ibrahim, Huda Hj; Azni, Syafiqah; Khamis, Shakiroh (Yayasan Sinergi Kawula Muda, 2024)
The Sistem Pengurusan Data Program Pemulihan Khas (SPD) is a web-based application that focuses on managing data for a remedial education program in 28 primary schools across Cameron Highlands, Pahang. It is a computerized system designed to replace the manual system that currently uses Microsoft Excel forms to manage pupils' information. The system's features enable tracking of the pupils' academic progress and providing data for upper management decision-making. This system is intended for use by remedial teachers to manage pupils' information, school authorities to monitor the program, and education officers at the district level. In developing the system, a system prototyping development methodology was adopted. Functional requirements were gathered through meetings with clients and a prototype called